1997
DOI: 10.1073/pnas.94.8.3736
|View full text |Cite
|
Sign up to set email alerts
|

RanBP2 associates with Ubc9p and a modified form of RanGAP1

Abstract: Ran is a small GTPase required for nuclear transport in eukaryotic cells [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 29 publications
2
161
0
2
Order By: Relevance
“…To promote export, TAP must interact with other components of the nuclear transport machinery+ Understanding the mechanism of TAP action during the export process requires the dissection, at the molecular level, of these interactions+ As a first step towards this end, we fractionated HeLa cell nuclear extracts by affinity chromatography and have identified putative TAP partners+ Recombinant TAP was expressed in Escherichia coli as a fusion with two immunoglobulin-binding domains of Protein A from Staphylococcus aureus at its N-terminus and an hexa-histidine tag at its C-terminus (zzTAP-6xHis)+ The recombinant protein was first purified on a Ni-NTA agarose column and then immobilized on IgG-Sepharose beads+ Binding of HeLa cell proteins to immobilized TAP was performed in the absence or in the presence of a mutant form of Ran that has a substitution of glutamine 69 for leucine (RanQ69L) (Klebe et al+, 1995 (Table 1)+ Proteins selected at high salt that were also present in the low-salt eluates were predicted to be prime candidates as TAP partners (Fig+ 2A, lanes 5, 6 vs+ 3, 4)+ Therefore, these proteins were excised from the gel, digested in gel with trypsin, and the subsequent tryptic peptides were identified by mass spectrometry+ The peptides sequenced unambiguously identify RanBP2/Nup358, CAN/Nup214, Nup88/Nup84, RanGAP1, and hGle2/RAE1 as the proteins migrating with apparent molecular weights of 350 kDa, 250 kDa, 89 kDa, 85 kDa, and 43 kDa (Fig+ 2A, lanes 5 and 6 and Table 1)+ Note that the apparent molecular weight of the selected RanGAP1 corresponds to that of its SUMOconjugated form (Matunis et al+, 1996;Mahajan et al+, 1997;Saitoh et al+, 1997)+ Strikingly, aside from CRM1 and hGle2, the proteins selected at high salt have all been localized to the cytoplasmic fibrils of the NPC (Fig+ 2B)+ Prompted by these observations we next identified proteins that, although present in substoichiometric amounts, were nevertheless reproducible selected under low salt conditions+ The identity of these proteins is indicated on the side of the gel (Fig+ 2A, lanes 3 and 4 and Table 1)+ Three of the proteins selected at low salt were identified as nucleoporins+ These were p205 (KIAA0225), Nup93 (Grandi et al+, 1997), and Nup98 (Radu et al+, 1995)+ Although p205 has not been defin-itively proven to be a nucleoporin, it forms a stable complex with Nup93 (Grandi et al+, 1997)+ Transportin and importin-b were also identified as proteins comigrating with Nup98 and Nup93, respectively (Table 1)+ Finally, a band migrating at approximately 160 kDa was identified as KIAA0169, a protein of unknown function, whereas a protein exhibiting an apparent molecular weight of 98 kDa was identified as E1B-AP5 (Gabler FIGURE 2. Identification of TAP partners+ A: HeLa cell nuclear extracts were incubated with IgG-Sepharose beads coated with zzTAP6xHis+ Binding reactions were performed in low salt (lanes 2-4 and 7) or in high salt (lanes 5 and 6) and either in the presence or absence of RanQ69L-GTP as indicated above the lanes+ After incubation and extensive washing, bound proteins were eluted and analyzed by SDS-PAGE followed by silver staining+ Lane 2 shows proteins eluted from the zzTAP-6xHis coated beads when nuclear extracts were omitted+ Lane 7 shows proteins eluted from the IgG-Sepahrose beads when TAP was omitted+ The identities of the selected proteins are indicated on the side of the gels+ B: Proteins selected on the TAP affinity column are shown on this schematical representa...…”
Section: Selection Of Nup98 and Three Npc-subcomplexes On Immobilizedmentioning
confidence: 90%
See 1 more Smart Citation
“…To promote export, TAP must interact with other components of the nuclear transport machinery+ Understanding the mechanism of TAP action during the export process requires the dissection, at the molecular level, of these interactions+ As a first step towards this end, we fractionated HeLa cell nuclear extracts by affinity chromatography and have identified putative TAP partners+ Recombinant TAP was expressed in Escherichia coli as a fusion with two immunoglobulin-binding domains of Protein A from Staphylococcus aureus at its N-terminus and an hexa-histidine tag at its C-terminus (zzTAP-6xHis)+ The recombinant protein was first purified on a Ni-NTA agarose column and then immobilized on IgG-Sepharose beads+ Binding of HeLa cell proteins to immobilized TAP was performed in the absence or in the presence of a mutant form of Ran that has a substitution of glutamine 69 for leucine (RanQ69L) (Klebe et al+, 1995 (Table 1)+ Proteins selected at high salt that were also present in the low-salt eluates were predicted to be prime candidates as TAP partners (Fig+ 2A, lanes 5, 6 vs+ 3, 4)+ Therefore, these proteins were excised from the gel, digested in gel with trypsin, and the subsequent tryptic peptides were identified by mass spectrometry+ The peptides sequenced unambiguously identify RanBP2/Nup358, CAN/Nup214, Nup88/Nup84, RanGAP1, and hGle2/RAE1 as the proteins migrating with apparent molecular weights of 350 kDa, 250 kDa, 89 kDa, 85 kDa, and 43 kDa (Fig+ 2A, lanes 5 and 6 and Table 1)+ Note that the apparent molecular weight of the selected RanGAP1 corresponds to that of its SUMOconjugated form (Matunis et al+, 1996;Mahajan et al+, 1997;Saitoh et al+, 1997)+ Strikingly, aside from CRM1 and hGle2, the proteins selected at high salt have all been localized to the cytoplasmic fibrils of the NPC (Fig+ 2B)+ Prompted by these observations we next identified proteins that, although present in substoichiometric amounts, were nevertheless reproducible selected under low salt conditions+ The identity of these proteins is indicated on the side of the gel (Fig+ 2A, lanes 3 and 4 and Table 1)+ Three of the proteins selected at low salt were identified as nucleoporins+ These were p205 (KIAA0225), Nup93 (Grandi et al+, 1997), and Nup98 (Radu et al+, 1995)+ Although p205 has not been defin-itively proven to be a nucleoporin, it forms a stable complex with Nup93 (Grandi et al+, 1997)+ Transportin and importin-b were also identified as proteins comigrating with Nup98 and Nup93, respectively (Table 1)+ Finally, a band migrating at approximately 160 kDa was identified as KIAA0169, a protein of unknown function, whereas a protein exhibiting an apparent molecular weight of 98 kDa was identified as E1B-AP5 (Gabler FIGURE 2. Identification of TAP partners+ A: HeLa cell nuclear extracts were incubated with IgG-Sepharose beads coated with zzTAP6xHis+ Binding reactions were performed in low salt (lanes 2-4 and 7) or in high salt (lanes 5 and 6) and either in the presence or absence of RanQ69L-GTP as indicated above the lanes+ After incubation and extensive washing, bound proteins were eluted and analyzed by SDS-PAGE followed by silver staining+ Lane 2 shows proteins eluted from the zzTAP-6xHis coated beads when nuclear extracts were omitted+ Lane 7 shows proteins eluted from the IgG-Sepahrose beads when TAP was omitted+ The identities of the selected proteins are indicated on the side of the gels+ B: Proteins selected on the TAP affinity column are shown on this schematical representa...…”
Section: Selection Of Nup98 and Three Npc-subcomplexes On Immobilizedmentioning
confidence: 90%
“…Nuclear transport occurs through the nuclear pore complexes (NPC) and depends on the presence of nuclear localization signals (NLSs) or nuclear export signals (NESs) in the transported molecules+ NLSs or NESs are recognized and bound by saturable import or export receptors that shuttle between the nucleus and cytoplasm+ Upon binding, the transport receptors dock their cargoes to the NPC and facilitate their translocation+ After delivering their cargoes, the receptors are recycled to initiate additional rounds of transport (reviewed by Görlich, 1997;Nakielny & Dreyfuss, 1997;Mattaj & Englmeier, 1998)+ A key regulator of nucleocytoplasmic transport is the small GTPase Ran (reviewed by Görlich, 1997;Dahlberg & Lund, 1998;Mattaj & Englmeier, 1998)+ Ran exists in a GTP-or GDPbound form+ The location of RanGAP1 primarily in the cytoplasm and RanGEF in the nucleus is believed to generate a nucleocytoplasmic gradient of RanGTP across the NPC that imparts directionality to the transport process (Görlich et al+, 1996;Izaurralde et al+, 1997;Richards et al+, 1997)+ Additional Ran cofactors are the Ran-binding protein 1 (RanBP1), which costimulates the activity of RanGAP1 (Bischoff et al+, 1995a(Bischoff et al+, , 1995b, and the Ran-binding protein 2 (RanBP2/Nup358) (Wu et al+, 1995;Yokoyoma et al+, 1995), which may have, in part, a similar function to RanBP1+ RanBP2/Nup358 is localized to the cytoplasmic fibrils of the NPC (Wu et al+, 1995;Yokoyoma et al+, 1995), whereas RanBP1 is predominantly cytoplasmic (reviewed by Görlich, 1997;Mattaj & Englmeier, 1998)+ A fraction of RanGAP1 conjugated with the ubiquitin-like molecule SUMO-1, binds to RanBP2 and localizes to the cytoplasmic fibrils of the NPC (Matunis et al+, 1996;Mahajan et al+, 1997;Saitoh et al+, 1997)+ Transport receptors identified to date are members of a large family of RanGTP-binding proteins exhibiting limited sequence similarity with the Ran-binding domain of importin-b (Görlich et al+, 1997;Fornerod et al+, 1997b), and have been termed importins/exportins or karyopherins+ The interaction of these b-related receptors with their cargoes or with nucleoporins is regulated by the binding of Ran to the receptor (reviewed by Mattaj & Englmeier, 1998)+ During export, the binding of RanGTP to the receptor is required for interaction of the receptor with its cargo and probably for the binding of the receptor to the pore+ The opposite situation exists d...…”
Section: Introductionmentioning
confidence: 99%
“…Its nucleotide-bound state is regulated by the Ran-specific GTPase-activating protein, RanGAP1 [23], and the specific guanine nucleotide exchange factor, RCC1 [24,25]. RanGAP1 is cytoplasmic or attached to the cytoplasmic margin of NPCs after conjugation with a ubiquitin-like protein [26][27][28], whereas RCC1 is exclusively nuclear and bound to chromatin [25,29]. The asymmetric subcellular distribution of the both Ran regulators is thought to result in a high concentration of RanGTP in nucleus, but low in cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid residue before Lys 532 is arginine, which is not a hydrophobic amino acid residue; however, because this lysine resides in a domain that is highly conserved among all members of NFAT family, we included Lys 532 in our analysis as well. Each of the three lysines was mutated individually to arginine, and the resulting NFAT1 point mutant cDNA clones were in vitro transcribed and translated into 35 S-labeled proteins and analyzed in the in vitro sumoylation assay (Fig. 2B).…”
Section: Identification Of Nfat1 As a Sumoylation Substrate-tomentioning
confidence: 99%